2021
DOI: 10.1038/s41420-021-00663-1
|View full text |Cite
|
Sign up to set email alerts
|

Single-cell RNA transcriptome reveals the intra-tumoral heterogeneity and regulators underlying tumor progression in metastatic pancreatic ductal adenocarcinoma

Abstract: Pancreatic ductal adenocarcinoma (PDAC) is the most frequent and aggressive pancreatic tumor characterized by high metastatic risk and special tumor microenvironment. To comprehensively delineate the complex intra-tumoral heterogeneity and the underlying mechanism during metastatic lesions malignant progression, single-cell RNA sequencing (scRNA-seq) was employed. PCA and TSNE were used for dimensionality reduction analysis and cell clustering. Find All Markers function was used to calculate differential genes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(20 citation statements)
references
References 48 publications
(52 reference statements)
3
17
0
Order By: Relevance
“…These molecules form a ligand–receptor web, guiding the crosstalk between cancer cells and nontumoral cells ( Figures 5D, E ). Unlike other single-cell studies in pancreatic cancer that analyze general ligand–receptor–directed cell interactions ( 19 , 48 , 49 ), we focused on intercellular crosstalk directed by the hub genes within coexpression networks. Under this prerequisite, the main participators in the network were fibroblasts and endothelial cells, which are frequently connected to tumor cells.…”
Section: Discussionmentioning
confidence: 99%
“…These molecules form a ligand–receptor web, guiding the crosstalk between cancer cells and nontumoral cells ( Figures 5D, E ). Unlike other single-cell studies in pancreatic cancer that analyze general ligand–receptor–directed cell interactions ( 19 , 48 , 49 ), we focused on intercellular crosstalk directed by the hub genes within coexpression networks. Under this prerequisite, the main participators in the network were fibroblasts and endothelial cells, which are frequently connected to tumor cells.…”
Section: Discussionmentioning
confidence: 99%
“…Xu et al have shown the utility of scRNA-seq in characterizing tumor heterogeneity in liver metastases from PDAC [ 45 ]. Their analysis identified multiple lineages of cancer cells within metastatic lesions, including five different types of ductal cells, and temporal trajectory mapping for cell lineage evolution was performed to elucidate the origins of cells within the metastatic lesions under investigation, highlighting the role that scRNA-seq has in predicting the composition of metastatic lesions or primary PDAC when tissue is only available from one source, as well as investigating the driver mutations behind neoplastic progression and dissemination.…”
Section: Discussionmentioning
confidence: 99%
“…Graphs were designed with the Seurat package in R as previously described. The ductal signature was clustered according to a 9-genes score identified in Xu et al, [ 28 ]. To analyze Moffitt subtypes, cells from each patient were clustered using the FindClusters function in Seurat with a resolution of 0.5.…”
Section: Methodsmentioning
confidence: 99%